NAVIGATING NUTRITION BEHIND BARS: A PHENOMENOLOGICAL STUDY OF PREGNANT INMATES’ PERCEPTIONS - Prastiwi, Ratih Sakti; Qudriani, Meyliya; Nisa, Juhrotun (Journal of Advanced Nursing and Health Sciences, 2025)
Background: Correctional institutions had made efforts to provide supplemental nutrition for pregnant inmates. This study examined how incarcerated pregnant women understand and respond to the nutritional conditions they face, with particular attention to their perceptions, attitudes, and sense of agency in meeting their dietary needs during imprisonment.Methods: A qualitative phenomenological approach was used. Between January and March 2024, data were collected through in-depth interviews and participant observation with six pregnant inmates in a women’s correctional facility in Indonesia. Thematic analysis was then conducted to identify key patterns and meanings in their experiences.Results: The analysis identified two main themes: Perceptions and Experiences About Nutrition and Strategies to Meet Nutritional Needs. Participants viewed prison food as inadequate and often inappropriate for pregnancy, with some expressing feelings of being uncared for. Food was also linked to moral and emotional meanings, including shame and judgment. To cope, women adopted informal strategies such as food sharing, small jobs, or saving money. However, limited nutritional knowledge influenced their choices, leading to misconceptions about what foods were healthy or suitable during pregnancy. Conclusion: These findings suggest that supporting pregnant inmates’ nutritional needs requires more than simply providing food. Emotional, cultural, and social factors should be considered in designing interventions. Collaborative programs, such as group prenatal classes or discussion forums, supported by culturally sensitive educational materials, and policies that support collaboration between prisons, healthcare providers, and community organizations, can help promote healthier behaviors and better support the well-being of pregnant women in custody.